From National Biosecurity Measures to Territorial ASF Preparedness: The Case of Free-Range Pig Farming in Corsica, France - Gisclard, Marie; Charrier, François; Trabucco, Bastien; Casabianca, François (Frontiers in Veterinary Science, 2021)
In response to African Swine Fever (ASF) outbreaks in wild boars in Belgium in 2018, the French authorities issued national biosecurity measures for all pig farms, regardless of their geographical and socio-technical scale. In Corsica, where free-range farming predominates, pig farmers protested that it was impossible to implement the measures (for geographical, cultural and economic reasons) and that their traditional farming system was in danger of extinction. This article questions the suitability of standardized top-down national measures that potentially endanger traditional breeding systems, which are increasingly marginalized in relation to the dominant industrial model. The authors, taking an action research approach, report on the design of a territorial preparedness plan in Corsica by a Technical Committee made up of actors from various regional research and development bodies concerned with animal health. Mediating between Corsican farmers and the authorities, the Committee drew up a socially acceptable preparedness proposal that goes beyond the usual classic biosecurity issues. Viewing the health risk from a local standpoint, the committee provided arguments for maintaining the extensive grazing that is non-negotiable for the farmers, while getting the farmers to agree to change other practices (reproduction control) as a measure against health hazards already present. Analysis of the preparedness process and the mediation process shows that a territorialized bottom-up approach to the governance of health risks can make biosecurity measures more acceptable to farmers. It also points to the legitimacy of a set of alternatives to top-down measures that standardize farming systems and may lead to the disappearance of small farmers and their traditional systems.